A critical study of Ibn Sina's economic ideas - Nurizal Ismail (International Institute of Islamic Thought and Civilization (ISTAC),International Islamic University Malaysia, 2012)
This study explores the economic ideas of Ibn Sina in household and political economies. The study also discusses the relevance of Ibn Sina's economic ideas on modem micro and macroeconomics ideas. According to Sabri Orman, the economic ideas of Ibn Sina can be traced and found in his practical philosophy, which is divided into three headings: Akhlaq (ethics), 'ilm Tadbir al-Manzil (economics) and 'ilm Tadbir al-Madlnah (politics). This study explains that household and political economies should be handled together, centered on Islamic values in the state. Findings of this study explain that the economic ideas of Ibn Slna are mostly related to the literature of 'ilm Tadbir al-Manzil (economics) and 'ilm Tadbir al-Madlnah (politics) that are related to modem micro and macro economics. Firstly, Ibn S!na's microeconomics focuses on man as the agent of economy and his own activity in managing wealth. This gives us a model of managing wealth from Ibn Slna that consists of kasb (earning) and infliq (spending). The kasb (earning) is from al-tijarah (trade) and a/-- ina 'at (manufacturing skills), while the infaq is the function of in{aq ijtima'I (common expenditure), in{aq dfni (religious expenditure) and al-iddikhar (savings). The kasb and the infaq are important variables of managing wealth. Secondly, Ibn Slna's macroeconomics focuses on the government's role on welfare in the state by regulating the law of economy, providing job opportunities and ensuring social security. This concept emphasizes that the state should also be responsible for social interests (ma=alih mushtarakah) and common funds (mal mushtarak) to conduct a balanced economy in society. This macroeconomics can be associated with the concept of the welfare state in today's world. Lastly, Ibn Slna's idea in economics is still relevant in the implementation of contemporary Islamic economics.